PENGADAAN SARANA DAN PRASARANA SEBAGAI PRAKTIK AMANAH DALAM MANAJEMEN PENDIDIKAN ISLAM: STUDI DI MADRASAH IBTIDAIYAH PANGKALPINANG - Andika Febriyanto; Sedya Santosa; Muhammad Nurul Arifin; Mu’aziz Latif (STKIP Pesisir Selatan, 2026)
This study aims to analyze the procurement of educational facilities and infrastructure from the perspective of Islamic Educational Management at Madrasah Ibtidaiyah Pangkalpinang. The research employed a qualitative approach with a case study design to obtain an in-depth understanding of the procurement process of educational facilities in madrasahs. Data were collected through interviews, observations, and documentation involving the principal, vice principals, and teachers. Data analysis was conducted through data reduction, data display, and conclusion drawing, while validity was ensured through triangulation. The findings revealed that procurement was carried out through planning, implementation, and utilization stages. Planning was conducted through internal deliberation by considering institutional needs and budget capacity. From the perspective of Islamic Educational Management, the procurement process reflected the values of trustworthiness, deliberation, efficiency, and responsibility. This study is expected to become a reference for improving the effectiveness of educational facilities management in madrasahs sustainably. However, post-procurement evaluation had not been conducted systematically, indicating the importance of strengthening planning, supervision, and evaluation in educational facilities management within madrasahs comprehensively.